Psychological function changes among house painters. - Hane, Monica; Axelson, Olav; Blume, Jan; Hogstedt, Christer; Sundell, Lennart; Ydreborg, Berit (Scandinavian Journal of Work, Environment & Health, 1977)
Nonspecific complaints such as fatigue, partial amnesia, loss of appetite, etc., have been reported by house painters and could be effects of occupational exposure to solvents. A random sample of union-affiliated house painters was compared for a number of parameters and psychological test results with a group of industrial workers having a corresponding age distribution. The groups proved to be on par in relevant background variables. A simple health cheok did not reveal ,any correlates to the subjective complaints, except for a somewhat lower hemoglobin concentration among the house painters. However, the painter group had significantly lower mean scores on psychological tests measuring intellectual capacity and psychomotor coordination than the reference group of industrial workers. The painter group also had significantly lower performances than expected on the memory test and the reaction time test. A discriminant analysis of indicators of change as derived from psychological tests, was carried out, and a point biserial correlation of 0.35 was obtained between the discriminant function and the dichotomous exposure variable defined by group affinity. Furthermore a study based on clinical patients, i.e., another body of data, indicated reasonable diagnostic validity for this discriminant function. Although no correlations were found within the painter group between exposure ("painter years") and the indicators of function change, rthe results indicate an effect of the work environment on health.
Keywords: brain damage; hemoglobin; hemoglobin concentration; house painter; painter; psychological function; psychological function test; solvent; work environment